Type-2bipolar-valued fuzzy comprehensive evaluation and its application in assessment of aerial targets - XIE Weihe, WANG Xueliang, LI Xiaofang, LIU Lin (Zhihui kongzhi yu fangzhen)
Regarding the rapid decision-making problem of complex information of aerial targets in surface ship air defense operations and based on the definition and basic operations of the type-2 bipolar fuzzy set, this article first proposes the type-2 intuitionistic fuzzy comprehensive evaluation method, and then applies it to the analysis and judgment of assessment of aerial targets, achieving certain good quantification, it provides an effective method for surface ship air defense combat multi-target complex information processing.